Modelo experimental em caninos para pesquisa de linfonodo sentinela do estômago - Torres de Melo, José Ricardo de Moura (2010)
The gastrectomy with extensive lymphadenectomy still is the gold standard for the dressing treatment of the gastric cancer (GC), even so these procedures can take high index of morbidity or mortality, mainly in the patients who do not present lymphatic dissemination of the illness. The research of sentinel lymph node (SLN), already consecrated in the initial tumors of breast and the melanomas, presents each time more frequent for upper gastrointestinal cancers, specially in GC with encouraging results. Studies initiated in the middles of 2000 portray increasing and sufficiently prosperous search for clarification of this question. The objective of this work is to elaborate an experimental model that can demonstrate technically, in laboratory, the research viability of SLN in gastric antrum of the dog. 25 female dogs had been studied with approach weight of 11 kg and age of 01/02 years, without definite race (WDR), healthful clinically, proceeding from the Control Center of Zoonosis of Fortaleza City with programming for euthanasia. With random choice, these animals had been studied individually and weekly. It was used, separately, radioisotopic 99mtechnetium labeled phytate and patent blue dye (V Guerbert 2.5%) injected at 01 cm above the piloro, on the small bending in the antrum gastric of the dog and analyzed in the times zero, 05, 10, 15 and 20 minutes. After this period, the injection place of the markers and gastric lymph nodes were appraised “in vivo” (in the animal) and the gastric lymph nodes “ex vivo” (out of the animal). For the study with the 99mtechnetium it was used the device Gamma Probe model Nuclearlab DGC-II (radioguiada surgery with sounding lead of irradiation connected to unit of counting and sonorous tracking) and for the patent blue dye, direct vision. For the analysis statistics were used the test of McNemar and the Quantify agreement with Kappa. The level of significance was established in 5% (p≤0,05). When the radioisotopic 99mtechnetium labeled phytate was used single, the LS was identified in 20 animals (80%). With the patent blue dye single, in 24 animals (96%). There is no statistic significance with the use of those markers for the LS research in the gastric antrum of the dog. The conclusions are (1) The stomach of the dog is adjusted for experimental model in alive research of the sentinel lymph node (2) The radioisotopic 99mtechnetium labeled phytate and patent blue dye (V Guerbert 2.5%) are efficients as markers of sentinel lymph node of the dog’s gastric antrum.